Avaliação da metodologia do Agroamigo em Caucaia-Ce - Maciel, Iracy Soares Ribeiro (2008)
The purpose of this dissertation is to evaluate BNB’s Rural Microcredit Program, the “Agroamigo”, under the perspective of the qualification of Pronaf Group B process of credit. This credit line of the National Program for Strengthening Family Agriculture (Pronaf) is designed to the poorest among the family farmers. The research involved 41 farmers in the municipality of Caucaia-CE besides the members of the different institutions that intermediate this public policy. Despite the adversities faced in the execution of the Program, the research reveals that the implementation of the referred methodology has added quality to the process of credit concession regarding the Pronaf B. The main results perceived are related to the following aspects: degree of comprehension of the financing conditions, adequacy of the credit to the farmer’s needs and to the kind of activity developed by him and his family, process agility, proximity and follow-up, payment rates and financing of non-agropecuary activities rates. In addition, we have investigated some aspects inherent to these farmers’ life conditions, to their way of organization and the social participation they develop, as well as to the interrelationship between them and the institutions which mediate the credit, and these institutions among themselves.